An improved indoor location technique using Kalman Filter - Fariz N.; Jamil N.; Din M.M.; Rusli M.E.; Sharudin Z.; Mohamed M.A. (Science Publishing Corporation Inc, 2023)
Indoor positioning technique is used to trace location of entities within a nonspace environment riding from the incapability of GPS to do so. Most of indoor localization techniques proposed by researchers aimed at discovering an optimized solution for indoor location tracking with high precision and accuracy. This paper proposes an improved indoor location technique by implementing Trilateration and Kalman Filter technique that can manipulate noise signal deduced from raw Received Signal Strength Indicator (RSSI). Upon implementing the technique, observation and comparison are made to measure the effectiveness and reliability of the enhanced Kalman Filter in tracking indoor positioning. Our analysis and finding shows that the enhanced indoor positioning technique improves the accuracy significantly. 2018 Authors.